Tetrahedron Effect: Connections Between the Central Bank Base Rate, Cash Holdings, Retail Deposits, Lending and Seigniorage in Hungary - Huszti, Ernő (Public Finance Quarterly, 2023)
The global financial crisis highlighted the key question as to how and with what efficiency the central bank and the business banking activities are connected under the conditions of the two-level bank system, which fairly solid and stable at present. The changes occurred in the ownership of financial institutions created novel relationships, with not only domestic but also foreign banks. The competition for clients has become natural, their relationship with the central bank strengthened and changed. These connections can be demonstrated through the special relations between interest, cash, deposits, the budget and the central bank. In the next years, the financial government will have to develop a toolkit that is able to ensure the appropriate compatibility of deposit creation, savings, lending and interest policy in the long run.